ショウワキチ フキン ノ カイテイ チケイ ダイ15ジ エットウタイ チリ ブモン ホウコク 1 - 森脇, 喜一; モリワキ, キイチ; MORIWAKI, Kiichi (国立極地研究所, 1975)
P(論文) An examination of research results of the continental shelf near Syowa Station suggests the fluctuations of the Antarctic ice sheet in connection with the eustatic change of sea level. Bathymetric charts of the areas near East Ongul Island and off the western part of the Prince Olav Coast were drawn, on the basis of sounding data of 980 points obtained by the author in 1974. The soundings were conducted with the echo-sounder which was developed in 1967 for the purpose of sounding from the surface of sea ice. Sampling of bottom sediments was attempted at 41 points in Lutzow-Holm Bay and near East Ongul Island, and 15 core samples of mud were obtained. The following are revealed by the examination of the charts: 1) Topographic trends near the Ongul Islands are in the north-south and east-west directions. They may be ascribed to glacial erosion which worked along the structural trend of foliations and joints of gneissic bedrock. 2) The fact that depressions and rises which, on the sea floor near the Ongul Islands, obviously extend north-south, suggests that the ice of this area in the past flowed from south to north. This direction of ice movement differs from the general east-west flow pattern of ice which is inferred from the glacial striae on the bedrock of East Ongul Island. These facts imply that the pattern of ice flow changed during fluctuation of the ice sheet. 3) The submarine topography near the Ongul Islands is discordant to the landform of the Ongul Islands, as the former shows large relief with steep slopes while the latter shows small relief within 40 meters in height. However, it remains unsolved whether or not the present sea level played a significant role in producing the contrast between subaerial and submarine topographies. 4) A narrow, long trough runs north-south from the northern corner of Liitzow-Holm Bay to off the western part of the Prince Olav Coast. This trough excavated the rise at a depth shallower than 200 meters. The longitudinal profile of the trough shows basin and sill ...